Cost Oriented Autonomous Mobile Service Robot. Issue 25 (2019) - Bula, Ines; Hajrizi, Edmond
Abstract: The high price of robots in the market, have created a barrier for most of people to have the prejudice that robots cannot be built without large funding The purpose of building the Cost Oriented Autonomous Mobile Service Robot from mechatronic scrap, first was to educate students in building this robot and second to improve that robot can be built entirely from scrap with 16 euro cost! Scrap robots can be a good tool for inspiring young students of all ages and the concept can have an added benefit as it helps the environment. This robot build from scrap is limited to its function and ability but is cost effective and building them was very educational for students in mechatronics field. The goal was to develop an autonomous robot that could move, find the way in/out in unknown environment, offering the services at the dentistry clinic, where the robot waits the patient, informs the doctors that there is a new patient, and brings the message of the doctor to the patient, without having to run by anyone. For this robot are used: Arduino Uno, two drive motors, a L298 double H-bridge driver, a servo motor, an ultrasonic distance meter, all from mechatronic scrap.